MATERUNA NYOMAN INFORMAL EDUCATION IN DEVELOPING TERUNA CHARACTER IN TENGANAN PEGRINGSINGAN, KARANGASEM - Juliawan, I Nengah (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2021)
AbstractEducation is an effort to produce quality of human resources. Formal and informal education are away of cultural inheritance to the younger generations therefore their cultural traditions can survive and develop in the midst of Indonesian society. One of the traditions that live in Bali with traditional education system is the Materuna Nyoman tradition. The Materuna Nyoman tradition is a series of ceremonies that has the aim of changing the status of teenage stage to adults stage according to custom. During the procession of a series of ceremonies is rich of meaningful education that form the character of adolescents into personal and responsible characters. Materuna Nyoman tradition needs to be educated to young leaners in Tenganan Pegringsingan to determine changes in the character of adolescents in Materuna Nyoman's education. This study was a qualitative research with an ethnographic research approach. Data was collected using the observation method, interview method, literature method. Collected data was analyzed using the interpretive descriptive analysis method. The analysis was carried out during and after data collection. With the activity steps to reduce data, present data, and carry out verification to make conclusions. The results showed that: (1) the process of the Nyoman Materuna series, namely Maajak-ajakan, Melali, Basen Pamit, Padewaraan or kagedong, Matamiang, Malegar, Ngintarang Katekung, Namiu Katamiu, Ngejot Gede, Ngetog, Katinggah. The characters formed in the participants of Materuna Nyoman are responsible for themselves and the village environment.Keywords: Materuna Nyoman Tradition, Education, Character.